2012
DOI: 10.1021/ac300689s
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Paper Network Format That Enables Simple Multistep Assays for Use in Low-Resource Settings in the Context of Malaria Antigen Detection

Abstract: The lateral flow test has become the standard bioassay format in low-resource settings because it is rapid, easy to use, low in cost, uses reagents stored in dry form, and is equipment-free. However, lateral flow tests are often limited to a single chemical delivery step and not capable of the multi-step processing characteristic of high performance laboratory-based assays. To address this limitation, we are developing a paper network platform that extends the conventional lateral flow test to two dimensions; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
259
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(260 citation statements)
references
References 26 publications
0
259
0
1
Order By: Relevance
“…AuNPs/Al 2 O 3 sol-gel/SPE was three times more sensitive compared to unmodified/bare SPE for the same concentration of analyte. Recently, Fu et al [59] developed a device consisting on a two-dimensional paper network signal-amplified immunoassay for malaria protein PfHRP2 detection. The paper card contains reagents stored in dry form, including an antibody conjugated to a gold particle label, and the user only needs to add water and the sample.…”
Section: Detection Methods Using Nanogoldmentioning
confidence: 99%
“…AuNPs/Al 2 O 3 sol-gel/SPE was three times more sensitive compared to unmodified/bare SPE for the same concentration of analyte. Recently, Fu et al [59] developed a device consisting on a two-dimensional paper network signal-amplified immunoassay for malaria protein PfHRP2 detection. The paper card contains reagents stored in dry form, including an antibody conjugated to a gold particle label, and the user only needs to add water and the sample.…”
Section: Detection Methods Using Nanogoldmentioning
confidence: 99%
“…The existing sequential flow devices either introduce valving mechanisms into pumping systems, such as paper-based microfluidic circuits, 39,40 or build integrated micropumps based on the flow control structures, such as the Quake systems. 33 In our work, pneumatic diaphragm microvalves are integrated into an mlSIP device since both of the fluidic actuation and the diaphragm microvalves are built with multi-layer structures and driven by the vacuum pressure, 49 which is described as unified pumping and control.…”
Section: Automatic Microfluidic Sequential Handlingmentioning
confidence: 99%
“…Microfluidic sequential flow devices have been developed for bioassays, such as pneumatic microvalve-based systems, [30][31][32][33] capillary-based systems, [34][35][36][37][38][39][40] the SlipChip systems, [41][42][43] and manual valving systems. 44 For most of these systems, liquid pumping process and flow control functions are separately driven by different accessory equipment, which ultimately increases the system complexity and the overall cost.…”
Section: Introductionmentioning
confidence: 99%
“…12 The flow rate of a fluid through the paper channel is proportional to the channel's cross-sectional area, length, and permeability and to the fluid's viscosity. Several researchers have attempted to change the permeability 8,[13][14][15][16] of paper to control the fluid flow. In particular, Chu et al 8 and Lutz et al 14 demonstrated lateral flow control by changing the permeability via infiltration of sugars into paper strips.…”
Section: Introductionmentioning
confidence: 99%